Mastercard : marketing transformation for a new world - Rosenthal, Jean, (SAGE Knowledge. Cases., 2018)
When Raja Rajamannar became Mastercard's CMO in 2013, the company was doing well. He inherited a marketing department that had led one of the most successful brand-building campaigns in history. And yet, there were ongoing changes in consumer behavior and use of technology that required reevaluating the department's strategy. At the point of purchase, users were often indifferent to their choice of card, basing their selection on factors such as functional benefits from an issuing bank rather than a positive desire for any given payment network. Customers had become more sophisticated, shifting loyalty to brands linked to their "passion points" rather than to products and services. Rajamannar decided that changes in consumer behavior and use of technology required Mastercard to substantially alter the company's marketing strategy. Believing that the company needed to inspire customers to create their own stories, he guided his department to build experiential platforms that would emotionally connect with the passion points of customers and encourage them to connect with Mastercard. As with any substantial change such as this, Mastercard faced questions of whether the new approach would work. Did it better leverage the features of the new consumer landscape? And more importantly, did it help Mastercard reach new consumers, merchants, and banks? And how should the company measure the success of the new programs?